[I111] Modern educational techniques in medical physics - Buchgeister, Markus (Physica medica, 2018)
Medical Physics can be taught to a variety of audiences: medical physics students, physicians, technical assistants, nurses and maybe also to the interested public. Teaching in the past and maybe still today uses often a lecture style: one is speaking, using the black board or Powerpoint presentations, all others are listening, trying to follow. Modern educational methods employ audience activating methods to pick up the individuals at their starting knowledge level and get them practically involved with the subject. Therefore, it is important to evaluate the starting knowledge of the participants and to adjust the course for the persons present accordingly. This can be done by anonymous introductory written tests or online feedback tools. Besides providing basic theoretical input at the start, by experience the intended subjects are best taught in a problem based style. This means to give one or a set of problems to individuals and groups formed from audience present. This can be done e.g. with the help of an online questionnaire in learning management systems like moodle to optimize the mixture of group members for best peer interaction. It is now the discussion within the groups, that get them actively in touch with the subject on way to the solution. It is no longer having all eyes watching one person, but have this person watch and accompany all other persons present on their way of discovering steps to one or more solutions of the problem given. Naturally, for this purpose they use information from the internet as well as one would do in real live, too. This can even be done in a competitive manner to enhance the emotional level of involvement. It is now the task of the teacher to provide basic knowledge, guide to good sources of information and to come up with appropriate problems and tasks. To facilitate this, a network of interested teachers in Medical Physics could exchange their set of concepts as “open educational resources” (OER) as well as collections of slides, images, graphs, animations and videos produced under GPL licence under the coordination of the EFOMP Education and Training Committee.